Jerónimo Martins international strategic expansion into the colombian market - Esguerra, Rodrigo Laserna (2017)
Having existed for more than two decades in the Portuguese and Polish markets, Portuguese familyowned Jerónimo Martins group established operations in Colombia under the brand Ara in 2013. After a careful research and detailed analysis, the Company decided to begin its business in the Colombian zona cafetera. Three characteristics of the region’s market motivated the location choice: (1) High population density and (2) market size and (3) low developed competitors, yet somewhat removed from the biggest Colombian clusters allowing greater experimentation freedom. After a successful launch and positive results, the company entered the caribbean coastal region. Capitalizing in its previous internationalization experiences, the company was able to successfully adapt to the particularities of the caribbean costal region market offering clients specific products according to their cultural preferences and well as an environment with which they feel identified. This strategy has allowed Ara to enjoy widespread popularity leading to the announcement by the Jerónimo Martins group about an ambitious Colombian national expansion plan on 2016. This case presents the Jerónimo Martins background, as well as the considerations that led the company to enter Colombia. It discusses the characteristics of the coffee region, and the caribbean costal area and how Aras success in these regions relates to the lessons learned by the Jerónimo Martins Group in its previous internationalization experiences. In particular, this discussion focuses on how having experimented with strategies such as alliances, joint ventures and acquisitions in its internationalization strategy, Jerónimo Martins Group’s constant search for long-term growth opportunities provided two valuable lessons (i) the know-how of how to develop business models specific for each market, and (ii) the awareness and flexibility to adapt to cultural differences in order to secure market position while maintaining long-term sustainability and maintenance of enterprise risk. These lessons have been capitalized and turned into landmarks of Jerónimo Martins expansion strategy. These strengths are expected to play an increasingly important role as the company expands to other areas of Colombia, a country known for its sharp regional cultural differences. Moreover, the Colombian national expansion plan is expected to pave the road for the Portuguese group to continue consolidating itself as a main player in the food retail sector in this Latin American destination. The case was created using information from the group, national and international data sources and interviews with some of the group’s employees. It has the information for the end of 2015, to allow students to understand the evolution of the group and of the entrance into the Colombian market.